2014
DOI: 10.1007/s40596-014-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Suicidal Behavior Among Graduate Students

Abstract: Graduate students experience significant amounts of stress and anxiety, and their suicidal behavior is strongly characterized by depression, hopelessness, desperation, lack of control, and eating problems. Future work with this population should focus on the development and evaluation of mental health and wellness interventions and on ways to promote help-seeking, especially among male students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 30 publications
2
81
1
4
Order By: Relevance
“…Other studies specific to college students have found that physical activity and dietary habits are related to motivation and perceived barriers (Downes, ). In general, college and graduate students have been found not to engage in the levels of physical activity and nutritious diets recommended by the U.S. Department of Health and Human Services and the U.S. Department of Agriculture (; Downes, ; Garcia‐Williams, Moffitt, & Kaslow, ; Office of Disease Prevention and Health Promotion, U.S. Department of Health and Human Services, n.d.; Rye et al, ). However, it is not currently known how healthy lifestyle behaviors and beliefs correlate with depression and anxiety in graduate health sciences students.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies specific to college students have found that physical activity and dietary habits are related to motivation and perceived barriers (Downes, ). In general, college and graduate students have been found not to engage in the levels of physical activity and nutritious diets recommended by the U.S. Department of Health and Human Services and the U.S. Department of Agriculture (; Downes, ; Garcia‐Williams, Moffitt, & Kaslow, ; Office of Disease Prevention and Health Promotion, U.S. Department of Health and Human Services, n.d.; Rye et al, ). However, it is not currently known how healthy lifestyle behaviors and beliefs correlate with depression and anxiety in graduate health sciences students.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports do exist and vary substantially in numbers of participants, metrics assessed and where they are published ( Table 1; http://nagps.org/wordpress/wpcontent/uploads/2015/06/NAGPS_Institute_ mental_health_survey_report_2015.pdf) [7][8][9] . Among these limited studies, nearly all show that about half of graduate students surveyed expressed significant emotional or stressrelated issues, including depression and anxiety.…”
mentioning
confidence: 99%
“…Mental illness is very common among graduate students and can have irreparable side effects. Researchers have demonstrated that graduate students experience unusually high levels of anxiety and depression (Evans et al, 2018;Garcia-Williams, Moffitt, & Kaslow, 2014). Regarding suicide, approximately 7% of students had suicidal thoughts, 2% reported making plans, and 10% reported having attempted suicide in their lifetime GRADUATE SCHOOL (Garcia-Williams et al, 2014).…”
Section: Mental Illness Suicide and Seeking Helpmentioning
confidence: 99%